Reference equations for breathlessness during incremental cycle exercise testing. Issue 2 (11th April 2023) - Elmberg, Viktor; Schiöler, Linus; Lindow, Thomas; Hedman, Kristofer; Malinovschi, Andrei; Lewthwaite, Hayley; Jensen, Dennis; Brudin, Lars; Ekström, Magnus
Background: Exertional breathlessness is commonly assessed using incremental exercise testing (IET), but reference equations for breathlessness responses are lacking. We aimed to develop reference equations for breathlessness intensity during IET. Methods: A retrospective, consecutive cohort study of adults undergoing IET was carried out in Sweden. Exclusion criteria included cardiac or respiratory disease, death or any of the aforementioned diagnoses within 1 year of the IET, morbid obesity, abnormally low exercise capacity, submaximal exertion or an abnormal exercise test. Probabilities for breathlessness intensity ratings (Borg CR10) during IET in relation to power output (%predWmax ), age, sex, height and body mass were analysed using marginal ordinal logistic regression. Reference equations for males and females were derived to predict the upper limit of normal (ULN) and the probability of different Borg CR10 intensity ratings. Results: 2581 participants (43% female) aged 18–90 years were included. Mean breathlessness intensity was similar between sexes at peak exertion (6.7±1.5 versus 6.4±1.5 Borg CR10 units) and throughout exercise in relation to %predWmax . Final reference equations included age, height and %predWmax for males, whereas height was not included for females. The models showed a close fit to observed breathlessness intensity ratings across %predWmax values. Models using absolute W did not show superior fit. Scripts are provided for calculating the probability for different breathlessness intensity ratings and the ULN by %predWmax throughout IET. Conclusion: We present the first reference equations for interpreting breathlessness intensity during incremental cycle exercise testing in males and females aged 18–90 years. Reference equations for breathlessness intensity are of importance for research and clinical care. These are the first reference equations for breathlessness during incremental cycle exercise testing for use to assess and compare breathlessness severity. https://bit.ly/3XAeqbQ